Hamartin: An Endogenous Neuroprotective Molecule Induced by Hypoxic Preconditioning - Li, Sijie; Ren, Changhong; Stone, Christopher; Chandra, Ankush; Xu, Jiali; Li, Ning; Han, Cong; Ding, Yuchuan; Ji, Xunming; Shao, Guo (Frontiers in Genetics, 2020)
Hypoxic/ischemic preconditioning (HPC/IPC) is an innate neuroprotective mechanism in which a number of endogenous molecules are known to be involved. Tuberous sclerosis complex 1 (TSC1), also known as hamartin, is thought to be one such molecule. It is also known that hamartin is involved as a target in the rapamycin (mTOR) signaling pathway, which functions to integrate a variety of environmental triggers in order to exert control over cellular metabolism and homeostasis. Understanding the role of hamartin in ischemic/hypoxic neuroprotection will provide a novel target for the treatment of hypoxic-ischemic disease. Therefore, the proposed molecular mechanisms of this neuroprotective role and its preconditions are reviewed in this paper, with emphases on the mTOR pathway and the relationship between the expression of hamartin and DNA methylation.